Analysis of River Transport Service Levels on the Pontianak-Labai Hilir Village Route, Simpang Hulu District, Ketapang Regency - Desi, Regina; Said, Said; Mukti, Elsa Tri (Jurnal Teknik Sipil, 2024)
With Pontianak as its capital, Kalimantan Barat relies on river transport, including speedboats and klotok, as key transportation alternatives. Factors like service quality, safety, and convenience influence their use. The research focused on the Pontianak to Labai Hilir Village route in Ketapang Regency and analyzed user characteristics, Minimum Service Standards (MSS), Importance Performance Analysis (IPA), and Customer Satisfaction Index (CSI). Male users dominate, particularly those aged 15-25, with 44% using speedboats and 32% klotok. Many users are entrepreneurs with incomes of Rp 2,000,000-6,000,000, using these transports mainly for economic purposes. The study found that speedboats meet 78% of MSS and klotok 67% of MSS, per Indonesia"™s Minister of Transportation Regulation No. PM 61/2021. IPA identified key issues like speedboat capacity, safety, fleet size, and information availability. Klotok users highlighted inadequate cleaning facilities. The CSI values are 70.69% for speedboats and 67.80% for klotok, both categorized as "satisfied," indicating that overall service meets user expectations.Keywords: Klotok, River Transport, Minimum Service Standard, Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI)